2019
DOI: 10.1039/c9sc02056j
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium hydride alkene insertion and catalytic hydrosilylation

Abstract: The β-diketiminato magnesium hydride, [(BDI)MgH]]2, reacts with alkenes and catalyses their hydrosilylation with PhSiH3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 96 publications
(75 reference statements)
0
46
0
Order By: Relevance
“…Recently, a variety of alkene substrates have been shown to insert into the Mg-H bond of A, at high temperature on the day timescale. 24 However, even with prolonged heating, no reaction was observed for 3a or 3b with either 1-hexene or styrene. Conversely, 1a and 3a were found to undergo facile reaction with the terminal alkyne phenylacetylene.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…Recently, a variety of alkene substrates have been shown to insert into the Mg-H bond of A, at high temperature on the day timescale. 24 However, even with prolonged heating, no reaction was observed for 3a or 3b with either 1-hexene or styrene. Conversely, 1a and 3a were found to undergo facile reaction with the terminal alkyne phenylacetylene.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…Similar to the Nikonov's work, Hill et al reported a neutral NacNac-Mg hydride dimer ( DIPP NacNacMgH) 2 (9) as a catalyst for alkyne hydrosilylation. 94 The reaction of diphenylacetylene with PhSiH 3 slowly proceeded to give the b-(E)-vinylsilane in 95% yield in 30 days (Scheme 24). Unlike Al (8) catalysis under the Lewis acid-activation mode, 93 its isoelectronic monomeric magnesium hydride 9 0 was found to work via the classical innersphere pathway, involving alkyne insertion, followed by a metathesis reaction with a hydrosilane.…”
Section: Hydrosilylationmentioning
confidence: 99%
“…Furthermore, b-diketiminate-based catalysts,s uch as the dimeric b-diketiminate manganese hydride (Mn-1)a nd the dimeric b-diketiminatomagnesium hydride (Mg-1)i nF igure 3, were also developed for anti-Markovnikov alkene hydrosilylation. [54,55] Using Mn-1 as catalyst, aliphatic alkenes underwent anti-Markovnikov hydrosilylation to afford (E)-bvinylsilanes with 37-99 %c onversion, while the hydrosilylation of styrenes afforded a-vinylsilanes with 19-99 %c onversion through Markovnikov hydrosilylation.…”
Section: Catalysts With Bidentate Ligandsmentioning
confidence: 99%
“…The structures of dimeric b-diketiminate manganese and magnesiumhydride. [54,55] Scheme 7. Iron-catalyzed hydrosilylation of alkenes with phenylsilane.…”
Section: Catalysts With Bidentate Ligandsmentioning
confidence: 99%